Assessment of Nitrate, Nitrite, and Ammonia Levels In Palu Bay and Its Impact on Health: Analisis Kandungan Nitrat, Nitrit dan Amonia di Perairan Teluk Palu dan Dampaknya Bagi Kesehatan - Paundanan, Matius; Hikmah, Sitti Ainun (Universitas Muhammadiyah Sidoarjo, 2025)
Water pollution due to nitrate, nitrite, and ammonia content has become a significant issue in Indonesian waters, including Palu Bay, which has the potential to affect water quality and human health. This study aims to analyze the levels of nitrate, nitrite, and ammonia in Palu Bay waters and their impacts on human health. Water samples were collected from 10 observation stations in Palu Bay and then brought to the laboratory for analysis. The laboratory results were compared with the Water Quality Standards as set by the Minister of Environment Regulation of the Republic of Indonesia No. 51 of 2004 concerning Marine Water Quality Standards for Marine Biota. The results of the study show that nitrate concentrations varied between 0.326 mg/l and 1.199 mg/l, exceeding the established standard of 0.008 mg/l. Meanwhile, nitrite was found at very low levels (<0.003 mg/l) and was only slightly detected at a few stations, while ammonia concentrations ranged from <0.03 mg/l to 0.06 mg/l, still within the standard limit of 0.3 mg/l. High nitrate levels have the potential to cause water pollution and negatively impact aquatic ecosystems as well as human health, particularly through respiratory and digestive issues, and pose a risk to infants consuming nitrate-contaminated water. Although nitrite and ammonia levels were not significant, the presence of these compounds still requires monitoring. This study suggests the need for better water quality management to prevent long-term health impacts and damage to aquatic ecosystems.